ANALISIS KETERAMPILAN BERBICARA BAHASA JERMAN LEVEL A2 PADA MAHASISWA SEMESTER SATU PROGRAM STUDI PENDIDIKAN BAHASA JERMAN UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR TAHUN AJARAN 2018/2019 - sahat taruli siahaan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
Abstract This study aims to determine A2 level speaking skills in first semester students of the German language education program at University of HKBP Nommensen Pematangsiantar in the 2018/2019 school year. To find out the predicate of students' speaking skills, applied the German speaking A2 assessment criteria model for the category of adult learners (Erwachsene) from the Goethe Institut. This research is included in a qualitative descriptive study in analyzing the ability to speak A2 level. The data for this study came from five German speaking dialogues transcript part 1, five German speaking monologue transcripts part 2 and five German speaking monologue transcripts part 3 German language study program students University HKBP Nommensen Pematangsiantar on daily topics. After analyzing the transcript of the speech dialogue, the authors found that (1) German language education program students at the University of HKBP Nommensen Pematangsiantar had four levels of speaking skills, with the predicate